Wiley International Encyclopedia of Marketing 2010
DOI: 10.1002/9781444316568.wiem05007
|View full text |Cite
|
Sign up to set email alerts
|

Launch Strategies

Abstract: Decisions made during the launch phase are recognized as important drivers of new‐product performance. At the same time, a new‐product launch is often the single most costly step in the new‐product development process. This launch phase also involves large risks as this stage is often the make‐or‐break point for a product's life cycle. The present article summarizes the extant knowledge on successful launch strategies. It starts by discussing the differences between strategic and tactical launch decisions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For radical innovation [38] demonstrated that current market research are not reliable as the perceptions for the radical products are not controlled by the marketers and users own real-world experience. Moreover, for radical innovations the traditional testing is not well suited and leads to wrong product introduction to wrong consumers at the wrong times [34,35]. To support the uncertainty related to radical innovations (Breakthrough Products) and the incapability of conventional testing finding the right consumer who will drive the radical innovation is a crucial factor [22,23].…”
Section: Specific Challenges In Radical Innovationmentioning
confidence: 99%
“…For radical innovation [38] demonstrated that current market research are not reliable as the perceptions for the radical products are not controlled by the marketers and users own real-world experience. Moreover, for radical innovations the traditional testing is not well suited and leads to wrong product introduction to wrong consumers at the wrong times [34,35]. To support the uncertainty related to radical innovations (Breakthrough Products) and the incapability of conventional testing finding the right consumer who will drive the radical innovation is a crucial factor [22,23].…”
Section: Specific Challenges In Radical Innovationmentioning
confidence: 99%